Corporate governance, ownership structure and intellectual capital disclosure : evidence from Malaysia / Gan Kin - Gan, Kin (2010)

(untitled)
Since the Asian Financial crisis occurred in 1997, Malaysia has implemented important corporate governance reforms to identify and address weaknesses highlighted during the crisis. Malaysia is aggressively highlighting the importance of good corporate governance to maintain its competitive edge as well as a source for sustainable economic growth. Keenan and Aggestam (2001) stressed that the success and failure of organizations in the twenty-first century depends on good governance practices in creating and leveraging intellectual capital (IC). Further, Tayles et al., (2007) view that IC has attracted increasing interest in recent years as management recognizes the contribution it makes in their pursuit of competitive advantage. Studies have been conducted on corporate governance and voluntary disclosure in Malaysian corporations,however little is known about the influence of corporate governance on voluntary disclosure of IC. Thus, this study is motivated to fill this research void. The objectives of this study are to determine the nature and extent of IC disclosure (ICD) among companies listed in Bursa Malaysia and to investigate the relationship between corporate governance attributes, ownership structures and voluntary disclosure of IC. Using content analysis, a longitudinal study was carried out from years 2006 to 2008 on 162 top companies listed in Bursa Malaysia. The Statistical Package on Social Science (SPSS) 16 was used to analyse and test the hypotheses developed in this study. The research found that size of audit committees and financial expertises within the audit committees have an influence on voluntary disclosure of IC. In addition, ownership structure is able to explain the behavioural practices of voluntary disclosure of IC and its components. Results show that GLCs and OWNDIFFs voluntarily disclose information on IC. In contrast, FAMC strictly adhere to their secrecy of not disclosing more details than those stipulated by law. Empirically, this study provides evidence of the nature and extent of information disclosed voluntarily on IC on corporations in Malaysia. The results also indicate the significance and growing awareness of IC information reported in annual reports. Furthermore, it presents useful insights into IC reporting of the three different ownership structures. These disclosures tap into the richness of IC as well as provide insights on the type of IC in the respective companies listed in Bursa Malaysia. From a theoretical view, this thesis contributes towards the agency as well as institutional theory in explaining the relationship between corporate governance, ownership structure and ICD. This study may be of interest to the regulators as well as standard-setters in meeting the growing demand for intangible information to be incorporated in annual report and facilitate the further call for them to speed up their efforts in producing guidelines for a more consistent IC reporting framework.